Reinforced concrete building design project & project based learning (case study) / Nur Najwan Aizam Roshaidi - Roshaidi, Nur Najwan Aizam (2021)
As a professional civil engineer we need to follow all the requirement and standards code in building the construction. We need to follow all the details by UBBL to make sure the building are verified and can be used after the construction finished. If we did not comply with the law, our project might be affected in terms of cost, time and etc. As civil engineering part, we all know that to build a construction is not easy and sometimes it can be challenging. We must have a huge of knowledge about the construction such as designing reinforced concrete, time frame and etc. Next, we know 60% material that use in construction is concrete while other 40% is steel. Thus, designing reinforce concrete with the Code of Practice is crucial. One of the example designing reinforced concrete is crucial because we want to construct a building that will be use by client. Other than that, we need to know which supplier is the perfect one that can be collaboration in this project. This is because we need to make sure all the materials that we buy are cheaper from market price and the quality are the best among all the supplier. In this term we must have a big of knowledge to avoid from be scammed. For this project, Microsoft project software has been used to make sure the flow and time frame are follow in schedule. This project duration are 287 days. It started on 29 march 2021 and ended on 3 may 2022. For this time frame, it is acceptable because the duration time is average. For the design section we can see column design is the most critical part because it have a lot of calculation that sometimes can be confused. The beam design in this project is flanged beam so it not easy as rectangular beam. We need to be more careful because some of parts are different. All the design main reinforcement, deflection and cracking in this project are pass and can be used. Moving to prokon software, it shown us the actual value of the calculation and from that we can detect our error or false in the manual design calculation. It is good because we can redesign so the results with get similar in the software. For this project, different calculation percentage between manual design and prokon software are not more than 30% so the value is acceptable and can be used in the construction. Lastly, for bill quantities and taking off, all parts are used same catalogue to make sure all the price are fixed. In my opinion, the most challenging part is continuous because the calculation is long.